Inovasi dan Pengembangan Kurikulum di Abad 21 - Ulfa Amriani; Rahma Ashari Hamzah; Wisrayani Wisrayani; Nursafitri Nursafitri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Curriculum innovation and development in the 21st century are essential responses to global change, digital transformation, and future skill demands. Modern curricula no longer emphasize knowledge mastery alone, but also strengthen literacy, numeracy, critical thinking, creativity, collaboration, communication, and character building. Project-based learning is promoted as an effective approach because it encourages students to participate actively in solving real-world problems through collaborative, contextual, and meaningful learning experiences. Technology integration also plays a strategic role in creating flexible, personalized, and adaptive learning environments that respond to diverse student needs. However, its implementation still faces challenges, including unequal access to digital facilities, limited teacher readiness, infrastructure constraints, and the risk of digital distraction. Therefore, curriculum innovation must be supported by appropriate policies, teacher competence, and responsible technology use. Overall, the 21st-century curriculum is a strategic foundation for producing competent, creative, character-driven, and globally competitive learners who are ready to face future challenges.